Toward the Establishment of New Clinical Endpoints for Cystic Fibrosis: The Role of Lung Clearance Index and Cardiopulmonary Exercise Testing - Hatziagorou, Elpis; Kampouras, Asterios; Avramidou, Vasiliki; Toulia, Ilektra; Chrysochoou, Elisavet-Anna; Galogavrou, Maria; Kirvassilis, Fotios; Tsanakas, John (Frontiers in Pediatrics, 2021)
As Cystic Fibrosis (CF) treatment advances, research evidence highlights the role and clinical applications that both Lung Clearance Index and Cardiopulmonary Exercise Testing as endpoints within clinical trials. In the context of establishing new endpoints for CF trials, we explore the implementation of these two test outcomes on regular CF care. We present the role of these two methods in assessing disease severity and disease progression and intervention efficacy with considerations for future research.